2014
DOI: 10.5688/ajpe789169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Potential Impact of Pharmacist Counseling on Medication Adherence Using a Simulation Activity

Abstract: Objective. To evaluate the impact of counseling in a simulated medication adherence activity. Design. Students were randomized into 2 groups: patient medication monograph only (PMMO) and patient medication monograph with counseling (PMMC). Both groups received a fictitious medication and monograph. Additionally, the PMMC group received brief counseling. A multiplechoice, paper-based survey instrument was used to evaluate simulated food-drug interactions, adherence, and perceptions regarding the activity's valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
1
14
0
2
Order By: Relevance
“…This could be largely due to structured education, counseling, reinforcement and motivation offered by the pharmacist. The study results observed were similar to the study conducted by the Morisky et al [12][13][14]. The study highlights the need for a periodic interaction between pharmacist and patient which will helps in improving patient medication adherence behavior.…”
Section: Influence Of Counseling and Education On Medication Adherencesupporting
confidence: 81%
“…This could be largely due to structured education, counseling, reinforcement and motivation offered by the pharmacist. The study results observed were similar to the study conducted by the Morisky et al [12][13][14]. The study highlights the need for a periodic interaction between pharmacist and patient which will helps in improving patient medication adherence behavior.…”
Section: Influence Of Counseling and Education On Medication Adherencesupporting
confidence: 81%
“…There was a statistically significant effect of providing counseling and leaflets or pharmacy counseling on the level of compliance of pulmonary TB patients in taking TB drugs before and 2 weeks after the intervention (Karuniawati et al, 2019). Counseling activities are also beneficial in helping patients understand their treatment, advance treatment compliance and patient treatment satisfaction and accordingly improve clinical outcomes (Volino et al, 2014;Sanii et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Simulation studies offer the possibility to assess the performance of a variety of methods and parameters in relation to a known state (Burton et al, 2006). In adherence research, simulation studies have been used to estimate pharmacokinetic properties (Ding et al, 2012; Pellock and Brittain, 2016) or the impact of interventions to improve adherence (Slejko et al, 2014; Volino et al, 2014; Piette et al, 2015). Optimal methods of summarizing longitudinal adherence and ideal parametrization of sliding windows to identify underlying patterns have not yet been established for this type of data.…”
Section: Introductionmentioning
confidence: 99%